Free‐breathing steady‐state free precession cine cardiac magnetic resonance with respiratory navigator gating. Issue 4 (28th April 2014) - Moghari, Mehdi H.; Komarlu, Rukmini; Annese, David; Geva, Tal; Powell, Andrew J.
Abstract : Purpose: To develop and validate a respiratory motion compensation method for free‐breathing cardiac cine imaging. Methods: A free‐breathing navigator‐gated cine steady‐state free precession acquisition (C ine‐Nav ) was developed which preserves the equilibrium state of the net magnetization vector, maintains the high spatial and temporal resolutions of standard breath‐hold (BH) acquisition, and images entire cardiac cycle. Cine image data is accepted only from cardiac cycles occurring entirely during end‐expiration. Prospective validation was performed in 10 patients by obtaining in each three complete ventricular image stacks with different respiratory motion compensation approaches: (1) BH, (2) free‐breathing with 3 signal averages (3AVG), and (3) free‐breathing with Cine‐Nav . Results: The subjective image quality score (1 = worst, 4 = best) for Cine‐Nav (3.8 ± 0.4) was significantly better than for 3AVG (2.2 ± 0.5, P = 0.002), and similar to BH (4.0 ± 0.0, P = 0.13). The blood‐to‐myocardium contrast ratio for Cine‐Nav (6.3 ± 1.5) was similar to BH (5.9 ± 1.6, P = 0.52) and to 3AVG (5.6 ± 2.5, P = 0.43). There were no significant differences between Cine‐Nav and BH for the ventricular volumes and mass. In contrast, there were significant differences between 3AVG and BH in all of these measurements but right ventricular mass. Conclusion: Free‐breathing cine imaging with Cine‐Nav yielded comparable image quality and ventricular measurements to BH, and was superior to 3AVG.Magn Reson Med 73:1555–1561, 2015. © 2014 Wiley Periodicals, Inc.